The use of geometric effects in diagnosing ion density in ICF-related dot spectroscopy experiments - Perez-Callejo, G; Liedahl, D; Schneider, M; Rose, S; Wark, J (Elsevier, 2019)
We describe a method to calculate the ion density of High Energy Density (HED) cylindrical plasmas used in Dot Spectroscopy experiments. This method requires only spectroscopic measurements of the Heα region obtained from two views (Face-on and Side-on). We make use of the fact that the geometry of the plasma affects the observed flux of optically thick lines. The ion density can be derived from the aspect ratio (height-to-radius) of the cylinder and the optical depth of the Heα-y line (1s2p 3P1 → 1s 2 1S0). The aspect ratio and the optical depth of the y line are obtained from the spectra using ratios measured from the two directions of emission of the optically thick Heα-w line (1s2p 1P1 → 1s 2 1S0) and the ratio of the optically thick to thin lines. The method can be applied to mid-Z elements at ion densities of 1019 − 1020 cm−3 and temperatures of a the order of keV, which is a relevant regime for Inertial Confinement Fusion (ICF) experiments.